Effectiveness of Otago Exercise on Health Status and Risk of Fall Among Elderly with Chronic Illness - Stefanus Mendes Kiik; Antonius Rino Vanchapo; Maria Fitrya Elfrida; Muhammad Saleh Nuwa; Siti Sakinah (Fakultas Ilmu Keperawatan Universitas Indonesia, 2020)
Falls are a serious consequence of declining physical function. Otago exercise is a strength and balance training program designed to prevent falls and enhance health status among the elderly. This study aimed to investigate the effect of a 12-week Otago exercise intended to reduce the risk of falls and health status among the elderly with chronic illness in the social elderly institution. This quasi-experimental study employed a pre- and post-test design using a control group. The study involved an intervention group (21 respondents) and a control group (21 respondents). The sample used in this study were elderly living in a social elderly institution. The sample was selected using simple random sampling. The data were analyzed using Mann–Whitney test, independent t-test, and Chi-square test. Otago exercise significantly reduced the respondents’ risk of falling and enhanced their health status. Significant differences were observed between the two groups in terms of the risk of fall (p= 0.041) and health status (p= 0.011). Otago exercise significantly improves the health status and reduces the risk of falling among elderly with chronic illness. The exercise can be recommended for older adults with chronic illness in social elderly institutions and communities. Abstrak Efektivitas Latihan Otago terhadap Status Kesehatan dan Risiko Jatuh pada Lansia dengan Penyakit Kronik. Jatuh adalah konsekuensi serius dari penurunan fungsi fisik. Latihan Otago adalah program latihan kekuatan dan keseimbangan yang didesain untuk mencegah jatuh dan meningkatkan status kesehatan pada lansia. Penelitian ini bertujuan untuk menginvestigasi efek 12 minggu latihan Otago untuk menurunkan risiko jatuh dan meningkatkan status kesehatan pada lansia dengan penyakit kronik di Panti Sosial lansia. Penelitian Quasi-eksperimental ini menggunakan pre-post dengan kelompok kontrol. Kelompok intervensi dan kontrol masing-masing terdiri dari 21 responden. Sampel dalam penelitian ini adalah lansia yang tinggal di UPT Kesejahteraan Sosial Lanjut Usia Budi Agung Kupang. Teknik sampling yang digunakan adalah simpel random sampling. Data dianalisis menggunakan Mann-Whitney test, Independent t-test dan Chi-square test. Latihan Otago secara signifikan menurunkan risiko jatuh dan meningkatkan status kesehatan. Ada perbedaan signifikan antara kedua kelompok dalam hal risiko jatuh (p= 0.041) dan status kesehatan (p= 0.011). Latihan Otago secara signifikan menurunkan risiko jatuh dan meningkatkan status kesehatan pada lansia dengan penyakit kronik. Kata Kunci: lansia, latihan Otago, penyakit kronik, risiko jatuh, status kesehatan